Leisure time analysis and comparison of secondary school male students in terms of selected regions of Slovakia: a cross-sectional study - Bartik, Pavol; Adamcak, Stefan; Marko, Michal (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Accumulating evidence indicates that leisure time lowers stress and depression and improves your quality of life, thus being something worth making time for. However, most secondary school students do not make effective use of their leisure time. Aim of Study. Our study was aimed at analysing and comparing leisure time of secondary school male students in terms of selected regions of Slovakia. Material and Methods. A non- -standardized survey of leisure time was carried out through an intentional sampling with the survey group size of 1830 secondary school male students (aged 17.35 ± 0.82 years) who attended the final year (4th) of grammar and vocational secondary schools. Basic descriptive statistics and the chi-square test (χ2) were used to analyse and compare the data. Data on leisure time was collected from January to June, 2021. Results. After analysing the survey answers, on average 43.98% (n = 805) of the survey group declared 1 to 3 hours/day of leisure time during the working week vs 5 hours/day of leisure time during the weekend (p < 0.01). In terms of spending their leisure time being active was declared by 58.94% (n = 1078) of the survey group (p < 0.01). Conclusions. Leisure time of the survey group differs significantly in terms of hours/day, way of spending and interest area (p < 0.01; 0.05). An example is average leisure time of the survey group during the working week and weekend, because in terms of selected regions of Slovakia the results revealed statistical differences (p < 0.01; 0.05); in particular between the selected regions of western (Bratislava Region), eastern (Košice Region, Prešov Region) and northern (Žilina Region) Slovakia.
Keywords: leisure time; secondary schools; adolescent boys; selected regions of Slovakia